Tingkat Partisipasi Masyarakat dalam Pengendalian Fraud Keuangan Desa: Studi Kasus Desa Fafinesu B - Modesta Neno; Amanda Leontin Balenaen; Angela Bari; Gresly Tefbana; Lauensia Werang; Susana Purnamasari Baso (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The management of Village Funds is vulnerable to financial fraud when it is not supported by effective oversight mechanisms. One alternative form of control is community participation as social supervision in village financial management. This study aims to analyze the effect of community participation on the control of village financial fraud in Fafinesu B Village. The research employed a quantitative approach using a survey method. Data were collected from 30 community members selected through purposive sampling and measured using a five-point Likert scale. The data were analyzed using descriptive statistics and simple linear regression. The results indicate that the level of community participation in supervising village financial management is generally categorized as good, particularly in terms of public awareness of oversight responsibilities. However, access to information regarding the amount of Village Funds remains limited. The control of village financial fraud is also perceived as good, although the reporting climate for suspected irregularities is not fully considered safe. Regression analysis shows that community participation has a positive and significant effect on the control of village financial fraud. These findings confirm that strengthening community involvement contributes to transparency and accountability in village financial governance.